Prof. Dr. Abdulkadir Noyan: Professional and Academic Aspects - Ada, Turhan (DOC DESIGN INFORMATICS CO LTD, 2025)
Prof. Dr. Abdulkadir Noyan graduated from Kuleli Military High School, Medical Preparatory School, and Military Medical School. In 1911, he began his career as an assistant at Gulhane Military Medical School and Seririyat Hospital, later becoming a chief assistant and infectious disease specialist in 1913. Following the Balkan Wars, Noyan served as the Corps Hygiene Consultant in Canakkale. During World War I, he worked as Baghdad's VIth Army headquarters physician and range doctor. He played an active role during the most critical phases of the National Struggle. In 1927, Noyan was appointed as a professor. In 1941, upon attaining the rank of brigadier general, he became the 1st Army Health Inspector. By 1943, he had risen to the rank of major general and was appointed Head of the Health Department at the Ministry of National Defense. After retiring from military service in 1945, Noyan joined Ankara Faculty of Medicine as the founding dean of the Department of Internal Medicine, where he served until 1948. He retired fully in 1952.
Keywords: Abdulkadir Noyan; medicine; microbiology; Ankara University Faculty of Medicine; General & Internal Medicine